1999
DOI: 10.1002/hep.510300214
|View full text |Cite
|
Sign up to set email alerts
|

Impaired mesenteric leukocyte recruitment in experimental portal hypertension in the rat

Abstract: Increased incidence of septic complications in human and experimental portal hypertension has been documented. Because development of an inflammatory response is essential in defense against infectious agents, the aim of this study was to assess leukocyte-endothelial cell interactions in an experimental model of portal hypertension. Intravital microscopy studies showed that under baseline conditions, leukocyte rolling, adhesion, and emigration in mesenteric venules were similar in control, sham operated (SO), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 31 publications
1
12
0
2
Order By: Relevance
“…A deficiency in one of the three steps of leukocyte recruitment can result in an inability of neutrophils to infiltrate in a region of inflammation. Impaired leukocyte recruitment has been reported previously in mesenteric venules of portal hypertensive rats [20,21] and in a model of acute cholestasis [22]. These findings support further the hypothesis of an altered anti-bacterial response in the splanchnic circulation.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…A deficiency in one of the three steps of leukocyte recruitment can result in an inability of neutrophils to infiltrate in a region of inflammation. Impaired leukocyte recruitment has been reported previously in mesenteric venules of portal hypertensive rats [20,21] and in a model of acute cholestasis [22]. These findings support further the hypothesis of an altered anti-bacterial response in the splanchnic circulation.…”
Section: Introductionsupporting
confidence: 82%
“…However, other adhesion molecules, not studied in this experiment, could contribute to the deficient leukocyte recruitment in cirrhosis. Previously, it was already shown that there was a downregulation of L-selectin in portal hypertensive rats [20,21]. The reason why cirrhosis is associated with a decrease in expression of adhesion molecules on mesenteric venules is obscure.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Portal hypertensive rats exhibit markedly reduced leukocyte rolling, adhesion, and migration in mesenteric venules in response to the lipid proinflammatory mediators, platelet-activating factor and leukotriene B4. This observation indicates that portal hypertension could be associated with a defective inflammatory response [27]. In an elegant experimental study, Pérez-del-Pulgar et al [28] demonstrated that partial portal vein ligation of rats changed the number of peripheral leukocytes from 7.0 10 6 to 3.6 10 6 cells/mL (P = 0.05).…”
Section: Cellular Immune Responsementioning
confidence: 96%
“…Patients with cirrhosis exhibit systemic immune alterations that may promote the development of infections and BT. Advanced cirrhosis is associated with decrease in the cellular and humoral components of immune response, decreased activity of the reticuloendothelial system, decreased phagocytic capacity of Kupffer cells, as well as restricted recruitment of leucocytes in response to inflammatory stimuli due to portal hypertension-associated splanchnic hyperaemia [16][17][18] . The inflammatory response induced by BT, with the synthesis of cytokines, particularly tumor necrosis factor-alpha (TNF-α), interleukins and nitric oxide (NO) also increases intestinal barrier permeability, which, in turn, favours BT, thus creating a feedback in which BT promotes its own causative mechanisms [5] .…”
Section: Pathogenesis Of Btmentioning
confidence: 99%